Implementation of Teaching Campus Program for the Students Soft Skill Development - Alfiatul Maulida; Bernadetta Diansepti Maharani; Zaizafun Sintarana; Princessa Rakhita Enadi; Regine Aguilar Principe (Universitas Sarjanawiyata Tamansiswa, 2023)
The current study aims to determine the implementation of Teaching Campus Program designed by the Ministry of Education and Culture, Republic Indonesia to improve students' soft skills. This descriptive quantitative study used 4-Likert scale questionnaires. The present study invited forty-five university students who enrolled the first and second batch of the Teaching Campus Program. They are from thirteen higher education institutions in Indonesia. The results of this research found that the existence of a Teaching Campus improves the student learning outcomes in terms of the soft skills, namely Communication Skills, Commitment, Detail Orientation, Entrepreneur Skills, Flexibility, Integrity, Leadership, Lifelong Learning, Motivation, Self -Confident, dan Thinking Skills.